CFD modeling to evaluate the thermal performances of window frames in accordance with the ISO 10077. (15th September 2016) - Malvoni, Maria; Baglivo, Cristina; Congedo, Paolo Maria; Laforgia, Domenico
Abstract: The main goal of the EPBD (Energy Performance Buildings Directive) is the improvement of the energy performance of the European buildings. The internal comfort is critically dependent on the envelope that plays a key role in the thermal balance of the entire building. In particular, the windows are one of the most critical elements in terms of solar gains, heat losses and thermal bridges; therefore, the design of high efficiency frames is requested, both in cold and warm climate, but with different peculiarity. The UNI EN ISO 10077-2 provides a methodology to evaluate the frame thermal behaviour and it proposes the criteria to validate the numerical model. This paper presents a two-dimensional numerical method for the thermal behaviour evaluation of the frame sections using GAMBIT 2.2 and ANSYS FLUENT 14.5 CFD code. The results have been validated in accordance with the UNI EN ISO 10077-2. The standard ISO replaces the air gas with a fictitious material "air solid" into the cavities. Besides the simulation carried out with ideal gas entails higher internal surface temperature than the air solid case. Therefore, the standard ISO imposes preventive computational conditions. The proposed numerical method can be implemented for several frame profiles with different features in terms of geometry and materials, representing a valid support in the design of new high thermal performance frames. Highlights: The internal comfort of building depends on the windows thermal features. The windows represent approximately 30–50% of transmission losses through the envelope. The window design is strategic to reach high-energy performance building. A CFD model to evaluate the thermal performance of frame profiles is shown. The proposed CFD model is developed in accordance with the UNI EN ISO 10077-2.